(N|LEMENTARNAQ TEORIQ MUZYKIs (NTEORIQ U^EBNYH ZAWEDENIJs - (Ni(B.(Nw(B.(NsPOSOBINs; (Nr(B.(N{AWERDOWAs (NREDAKTORs ((NmOSKWAs (NmUZYKAs, 1979)
(Nu^EBNIK WYDA@]EGOSQ SOWETSKOGO MUZYKOWEDA I PEDAGOGA WY[EL W SWET W (B1951 (NGODU I UVE MNOGO LET [IROKO ISPOL_ZUETSQ W U^EBNOJ PRAKTIKE(B.s
Keywords: (NtEORIQ(B.s